Pekan Soft Clay Treated With Hydrated Lime As A Method Of Soil Stabilizer - Azhani, Zukri (Elsevier Ltd, 2012)
The main objective of this paper is to determine the optimum lime content (OLC) required for Pekan soft soil treatment program and its strength. The OLC will be determined using Eades-Grim pH test. Another testing that involved in this study are Atterberg Limit, Unconfined Compressive Strength and Standard Proctor Test. From the study, the optimum amount to stabilize the clay soil in this particular area and minimum amount of lime to raise soil pH level to 12 is 4%. The soil strength is reach 116kN/m2 while the maximum dry density and optimum moisture content for treated soil are 16kN/m3 and 13% respectively. All the samples tested reach a significant strength level when enough lime is provided. It can be concluded that, lime stabilization method can be used as a soil treatment program for Pekan Clay especially for road construction.